Zagadnienie zła w polemice Tertuliana z Gnozą - Adam M. Filipowicz (Studia Ecologiae et Bioethicae)
The article presents the views of Tertullian on the causes and origin of evil in the context of his polemic with heretics remaining under the influence of Gnostic thought. The analysis refers to the following treatises of Tertullian: Adversus Hermogenem, Adversus Valentinianos, Against Marcion, De anima, Apologeticum. The subject covers the following points: 1. Introduction. 2. the origin of evil. 3. Free will and choice between good and evil. 4. Responsibility for the evil that is the question of rewards and punishments.